Aberrant Intrinsic Connectivity of Hippocampus and Amygdala Overlap in the Fronto-Insular and Dorsomedial-Prefrontal Cortex in Major Depressive Disorder - Tahmasian, Masoud; Knight, David C.; Manoliu, Andrei; Schwerthöffer, Dirk; Scherr, Martin; Meng, Chun; Shao, Junming; Peters, Henning; Doll, Anselm; Khazaie, Habibolah; Drzezga, Alexander; Bäuml, Josef; et al. (Frontiers in Human Neuroscience, 2013)
Neuroimaging studies of major depressive disorder (MDD) have consistently observed functional and structural changes of the hippocampus (HP) and amygdale (AY). Thus, these brain regions appear to be critical elements of the pathophysiology of MDD. The HP and AY directly interact and show broad and overlapping intrinsic functional connectivity (iFC) to other brain regions. Therefore, we hypothesized the HP and AY would show a corresponding pattern of aberrant intrinsic connectivity in MDD. Resting-state functional MRI was acquired from 21 patients with MDD and 20 healthy controls. ß-maps of region-of-interest-based FC for bilateral body of the HP and basolateral AY were used as surrogates for iFC of the HP and AY. ANOVA was used to compare ß-maps between MDD and healthy control groups, and included covariates for age and gender as well as grey matter volume of the HP and AY. The HP and AY of MDD patient’s showed an overlapping pattern of reduced FC to the dorsomedial prefrontal cortex and fronto-insular operculum. Both of these regions are known to regulate the interactions among intrinsic networks (i.e. default mode, central executive, and salience networks) that are disrupted in MDD. These results provide the first evidence of overlapping aberrant HP and AY intrinsic connectivity in MDD. Our findings suggest that aberrant HP and AY connectivity may interact with dysfunctional intrinsic network activity in MDD.